Review article: studies of fungi in the state of Amazonas, Brazil in the last 10 years - Cavalcante, Felipe Sant' Anna; Campos, Milton César Costa; Lima, Janaína Paolucci Sales de (Ciência e Natura, 2022)
Fungi are eukaryotic beings, uni or multicellular and are present in our daily lives, both in the manufacture of food and in the proliferation of diseases. The occurrence of fungi of the phylum Basidiomycota is most frequently found in the forest, as it is in these places that fungi find the conditions that best guarantee their physiological needs, acting as the main decomposers of organic matter. The present work aims to carry out production analysis on fungi in Amazonas. The review consisted of analyzing scientific articles, dissertations and thesis in the field of mycology in the Amazon region available in the databases PubMed, Scielo, Lilacs, ScienceDirect and Google Scholar, in English and Portuguese. The data collection used the publication period between 2008 and 2018 as the inclusion criterion, the exclusion criterion was the keywords that were not in accordance with the analyzes proposed by the publication criteria. It was found that all related works on fungi are published in scientific journals in the areas of teaching (two), health (five) and the environment (four), with emphasis on the fungi Candida, Aspergillus and Penicillium. The Amazon Forest has been little investigated, mainly in relation to fungi research, which makes it urgent to know about the diversity of fungi, especially in areas of the Brazilian Amazon, where it needs to be measured.